Paternal involvement in a group of fathers of elementary school children - Simões,Rita (2010)
The purpose of this study was to evaluate the degree of paternal involvement in Portuguese parents of children between 5 and 9 years old, exploring factors of interindividual variability (father´s age, education, socioeconomic status and number of children), as well as the association between father involvement and a number of factors identified in the literature: parental satisfaction, parental stress and marital adjustment. The sample consists of 145 married fathers aged between 28 and 59 years (M = 40.14), most of them with a high and college degree of education and a middle socioeconomic status. Data collection was based on self-report assessment scales, along with a questionnaire for socio-demographic characterization. The main results point to a relatively high degree of paternal involvement, particularly in the dimensions Care and Availability, although in relative terms the fathers reports indicate a higher percentage of time given to mothers as primary caregivers of children. There were no significant differences between the fathers depending on the individual variables studied. However, we found a moderate negative association between father involvement and parental stress, and also a moderate positive association between father involvement and dyadic adjustment, which is consistent with other studies in this area. The results support the multidimensional conceptualization of father involvement, suggesting different dimensions of paternal behavior in relation to the care and education of children. In addition, the study confirms the multi-determined nature of paternal involvement, suggesting that personal and relational factors may have an impact on how men perform paternity.